STRATEGI PENGELOLAAN DANA ZAKAT, INFAQ DAN SEDEKAH (ZIS) PADA UPZ KECAMATAN DUKUN KABUPATEN GRESIK - Robbah Khunaifih; M. Masrur Huda Asjhadi; Duta Bintan Fitriyah; Nailis Sa’adah (Nusantara: Jurnal Pengabdian kepada Masyarakat, 2021)
Management of zakat funds requires an institution that handles it in a professional, trustworthy and accountable manner, starting at the central level to the regional level (read: at the lower level it is called UPZ). UPZ (Zakat Collector Unit) is an institution that collects as well as distributes or distributes zakat, formed and officially issued by the local regional BAZNAS. The purpose of its establishment is in accordance with the mandate of Law No.23 of 2011 concerning zakat, namely by becoming UPZ BAZNAS, UPZ operations have been standardized according to the principles of proper zakat management. The services provided by UPZ BAZNAS are more optimal with the authority to provide Evidence of Zakat Deposit (BSZ) printed by BAZNAS. The BSZ can be used as evidence that the zakat paid can be calculated as a deduction from taxable income (zakat as deductible items). One area in East Java in Gresik Regency, Dukun District, has formed a UPZ which is coordinated by the Dukun District UPZ Coordinator who oversees several UPZs, be it Village UPZ or Mosque UPZ and Taklim Assembly UPZ. The existence of the UPZ Coordinator is quite effective in coordinating the management of Zakat, Infaq and Shodaqoh (ZIS) for Muzakki (Zakat Givers), or Mustahik (Zakat Recipients) and Munfiq (Shodaqoh Givers). The potential of ZIS in Dukun Subdistrict, Gresik Regency is quite high, both from the trade, agriculture or animal husbandry sectors as well as from the professions through Professional Zakat. From the early 2017 formation of UPZ until 2021, there was a significant increase. From simply recording ZIS acquisitions to making direct deposits to BAZNAS Gresik, the nominal amount of potential starts from the acquisition of 800 million rupiah to more than 3.5 billion in 2021. This is none other than community participation after going through education and socialization from the Coordinator UPZ either through official or non-official forums such as Friday Khutbah, Tarawih Kultum or existing Taklim Assembly activities.